Patents granted to Peruvian universities in the biomedical field: 2010 to 2020 - César Félix Cayo-Rojas; Marysela Irene Ladera-Castañeda; Carlos López-Gurreonero; Luz Genara Castañeda-Pérez (Revista Habanera de Ciencias Médicas)
Introduction: A patent is an industrial property title granted by the State to the inventor of a new product or technology, susceptible of being marketed for profit on an exclusive basis for a determined period of time.